THE GERMAN ELECTORAL MODEL IN RESPONSE TO THE MACEDONIAN POLITICAL CONTENT - Naumovska, Bojana (Institute for Sociological, Political and Juridical Research, University "Ss. Cyril and Methodius" - Skopje, 2021)
Having regard the role of the electoral model on the political behavior of the citizens in a country, as well as the impact it has on the party system, this paper aims to offer a new electoral model that is most appropriate for the Macedonian political context. Guided by the characteristics of the electoral systems, as well as their application in specific state systems, the research question of this paper will focus on determining the adequacy of the German electoral model in relation to the detected shortcomings of the existing Macedonian electoral model. In order to answer the main research question, this paper, in addition to presenting the German election model, through the presentation and analysis of primary and secondary data will try to connect the detected shortcomings of the existing Macedonian model with the basic characteristics of the offered most appropriate model.
Keywords: electoral systems, German electoral model, Macedonian electoral model, electoral behavior